Linguacultural Analysis Of Holiday Names In English - Mengboyev Azizbek Alijon ugli (Periodica Journal, 2024)
This article explores the linguistic and cultural significance of holiday names in the English language. By analyzing their origins, meanings, and linguistic structures, the article aims to demonstrate how holiday names serve as a reflection of cultural values, historical events, religious traditions, and societal changes. Drawing on examples such as Christmas, Halloween, and Independence Day, the study highlights the interplay between language and culture, showcasing how these names preserve historical narratives, embody collective memories, and evolve over time. Furthermore, the article examines the role of English holiday names in cross-cultural communication, illustrating their global recognition, adaptation, and influence in diverse cultural contexts. Through this exploration, the study sheds light on the importance of holiday names as both linguistic markers and cultural symbols, contributing to a deeper understanding of how language reflects and shapes human experiences.
Keywords: linguocultural analysis; holiday names; English language